Construction of a Yeast Protein-Chitooligosaccharide W/O/W Emulsion System for Carrying and Stabilization of Betacyanins - Yichen Li; Jiaqi Ding; Yaxin Wu; Shihao Sun; Demei Meng; Chunkai Gu; Rui Yang (Foods)
Natural pigments like betacyanins are highly unstable under heat, light, acid, and alkaline conditions. Yeast protein (YP) is a promising substitute protein, while chitooligosaccharides (COS) are water-soluble alkaline polysaccharides. Water-in-oil-in-water (W1/O/W2) emulsions, with two-membrane, three-phase structure, can serve as effective carriers for stabilizing pigments. In this study, YP-COS complexes formed through electrostatic interactions were used as hydrophilic emulsifiers to create betacyanin-coated W1/O/W2 emulsions. The W1/O colostrum was designed to make up 30%, 70%, and 90% of the emulsion (v/v)and the W2 was designed by the complexes with three concentrations of YP (2%, 1.25% and 0.5%, w/v)-COS (6%, 3.75% and 1.5%, w/v). The optimal formulation was determined through comprehensive evaluation of micromorphological characteristics, particle size, zeta potential and creaming index, ultimately yielding a system comprising YP (2%)-COS (6%) and 90% W1/O colostrum. Moreover, the W1/O/W2 emulsion system significantly improved the betacyanins retention under thermal treatment, photolytic exposure, pH gradients, and extended storage compared to the betacyanin aqueous solution (p < 0.05). In vitro digestion tests showed the emulsion retained 58.39% of betacyanins, while the betacyanin aqueous solution retained only 41.42%, demonstrating the emulsion’s ability to delay the betacyanins release, offering new insights for using YP-COS complexes in food production and other fields.